Detomidine and the combination of detomidine and MK‐467, a peripheral alpha‐2 adrenoceptor antagonist, as premedication in horses anaesthetized with isoflurane. (22nd December 2014) - Pakkanen, Soile AE; Raekallio, Marja R; Mykkänen, Anna K; Salla, Kati M; de Vries, Annemarie; Vuorilehto, Lauri; Scheinin, Mika; Vainio, Outi M
Abstract Objective To investigate MK‐467 as part of premedication in horses anaesthetized with isoflurane. Study design Experimental, crossover study with a 14 day wash‐out period. Animals Seven healthy horses. Methods The horses received either detomidine (20 μg kg−1 IV) and butorphanol (20 μg kg−1 IV) alone (DET) or with MK‐467 (200 μg kg−1 IV; DET + MK) as premedication. Anaesthesia was induced with ketamine (2.2 mg kg−1) and midazolam (0.06 mg kg−1) IV and maintained with isoflurane. Heart rate (HR), mean arterial pressure (MAP), end‐tidal isoflurane concentration, end‐tidal carbon dioxide tension, central venous pressure, fraction of inspired oxygen (FiO2) and cardiac output were recorded. Blood samples were taken for blood gas analysis and to determine plasma drug concentrations. The cardiac index (CI), systemic vascular resistance (SVR), ratio of arterial oxygen tension to inspired oxygen (PaO2/FiO2) and tissue oxygen delivery (DO2) were calculated. Repeated measures anova was applied for HR, CI, MAP, SVR, lactate and blood gas variables. The Student's t‐test was used for pairwise comparisons of drug concentrations, induction times and the amount of dobutamine administered. Significance was set at p < 0.05. Results The induction time was shorter, reduction in MAP was detected, more dobutamine was given and HR and CI were higher after DET+MK, while SVR was higher with DET. Arterial oxygen tension and PaO2/FiO2 (40 minutes after induction), DO2 and venous partial pressure of oxygen (40 and 60 minutes after induction) were higher with DET+MK. Plasma detomidine concentrations were reduced in the group receiving MK‐467. After DET+MK, the area under the plasma concentration time curve of butorphanol was smaller. Conclusions and clinical relevance MK‐467 enhances cardiac function and tissue oxygen delivery in horses sedated with detomidine before isoflurane anaesthesia. This finding could improve patient safety in the perioperative period. The dosage of MK‐467 needs to be investigated to minimise the effect of MK‐467 on MAP.